Neuroinflammation - Minagar, Alireza (Academic Press, 2018)
Neuroinflammation, Second Edition, discusses the role inflammation plays in neuro-inflammatory diseases. As research in neuroinflammation has dramatically increased in recent years, this new edition covers all of the new developments and findings since the first publication nearly a decade ago. Comprehensive coverage of topics includes chapters on multiple sclerosis, optic neuritis and Susac syndrome. New chapters cover the latest research in Epilepsy and Neuroinflammation, Pediatric MS, Pediatric Lupus and Traumatic Brain Injury, amongst other topics. Inflammation is a central mechanism in many neurological diseases, including stroke, multiple sclerosis, brain trauma and meningitis, and it contributes to the generation of pain. Researchers are now beginning to understand the impact of the immune system on different nervous system functions and diseases, ranging from damage, through tolerance, and to modulation and repair